Performance Analysis of Water Filtration Units for Reduction of pH, Turbidity, Solids and Electricity Conductivity - Laghari, A. N.; Walasai, G. D.; Jatoi, A. R.; Shaikh, F. A.; Siyal, Z. A. (Engineering, Technology & Applied Science Research, 2018)
The main objective of this study was to analyze the performance of different filtration units that reduce turbidity, pH, total dissolved solids (TDS) and electrical conductivity (EC) of canal water. For that, three different types of filtration units, namely, slow sand, rapid sand and dual media were fabricated. Typical parameters of canal and filtered water, like pH, turbidity, TDS and EC were examined, and then the filtered water quality was compared with World Health Organizations (WHO) standards. Maximum pH reduction was noted with dual media and less by the rapid system, while more turbidity was reduced with the slow sand and less with the dual media filtration system. In contrary to the pH and turbidity results, increment in both TDS and EC values were noted in filtered samples compared to that of raw water samples due to the transfer of dissolved minerals present in the sand into the filtered water during the contact period with media in the bed. However, all examined parameters of filtered water were within WHO standards.